The development of novice foreign language specialist’ creative potential based on acmeologic approach - Аkhmetova, B.B.; Kaskatayeva, Zh.A. (Ye.A.Buketov Karaganda State University Publishing house, 2015)
The article deals with the efficiency of acmeologic approach in developing creative potential of novice foreign language specialists’ for professional training in higher institution. Methodological-theoretical relevance of training would-be-teachers and determining new priorities in higher education system that will meet social and economic changes in modern community.
Акмеологиялық тұрғы негізінде болашақ шетел тілі мұғалімдерінің шығармашылық дайындығын дамыту
Развитие творческой готовности будущих учителей иностранного языка на основе акмеологического подхода
Keywords: creative personality; creative potential of personality; pedagogical acmeology; acmeological approach; acmeological position; personal qualities